2020
DOI: 10.2174/1871520620666200424102615
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In Vitro Anticancer, Anti-Inflammatory and DNA Binding Activity of Thiazolidinedione Derivatives

Abstract: Background: Cancer is the second leading cause of mortality worldwide. Despite of several advances made in the treatment strategies, cure for cancer remains still a challenge. Currently used treatment modalities pose several side effects and remain ineffective in the later stages. Thiazolidinediones (TZDs) have been shown to possess anti-cancer activity in several in vitro models. Objectives: The objectives of this study were to assess the effect of novel synthesized thiazolidinedione derivatives on three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…There have been several studies determining the anticancer effects of 4-thiazolidinone derivatives. More commonly studied derivatives are thiazolidine and 4-thiazolidinone, and it has been shown that these molecules have anticancer effects on several cancers including chronic myeloid leukemia, lung carcinoma, breast cancer, prostate cancer, oral cancer, colorectal cancer, neuroblastoma, and glioma [ 27 32 ]. While thiazolidine and 4-thiazolidinone derivatives exhibit different mechanisms of action to exert their anticancer effects, only a few of many studies reported their relation with autophagy pathways [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies determining the anticancer effects of 4-thiazolidinone derivatives. More commonly studied derivatives are thiazolidine and 4-thiazolidinone, and it has been shown that these molecules have anticancer effects on several cancers including chronic myeloid leukemia, lung carcinoma, breast cancer, prostate cancer, oral cancer, colorectal cancer, neuroblastoma, and glioma [ 27 32 ]. While thiazolidine and 4-thiazolidinone derivatives exhibit different mechanisms of action to exert their anticancer effects, only a few of many studies reported their relation with autophagy pathways [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the three N ‐Mannich bases 167 of a 5‐arylidene‐1,3‐thiazolidin‐2,4‐dione (Figure 20) that were described in a report [163] has been tested against MCF‐7 breast cancer cell line, and an IC 50 value of 1.27 μM was determined for it, while investigation of molecular mechanisms showed that compound 167 (X=O) induces apoptosis by affecting PI3 K/AKT/mTOR, VEGF and HIF‐1α signaling. In a collection of N ‐Mannich bases 168 (X=S or O) (Figure 20) derived from analogous 5‐arylidene‐1,3‐thiazolidin‐2,4‐diones, but having arylamines in the aminomethyl group, the most active three candidates in this series had IC 50 values between 30 and 70 μM against MCF‐7 breast adenocarcinoma, A549 lung adenocarcinoma or HT‐29 colorectal carcinoma [164] …”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Obtained ...mentioning
confidence: 97%
“…In a collection of N-Mannich bases 168 (X = S or O) (Figure 20) derived from analogous 5-arylidene-1,3-thiazolidin-2,4-diones, but having arylamines in the aminomethyl group, the most active three candidates in this series had IC 50 values between 30 and 70 μM against MCF-7 breast adenocarcinoma, A549 lung adenocarcinoma or HT-29 colorectal carcinoma. [164] Examples of aminomethylated benzimidazoles as anticancer agents have been scarce in recent literature. The most potent Mannich bases 169 (Figure 20) had a hydroxyl-substituted arylideneamino group (Ar is 2-, 3-or 4-HOC 6 H 4 ), but even these compounds were weak antiproliferative agents against MV4-11 human leukemia cell line compared to cisplatin, as their reported IC 50 values were in the range of approximately 2.1 to 4.8 mg/mL (6 to 12 mM), and these values were at least 50 times greater than the IC 50 value of cisplatin (0.04 mg/mL, or 0.13 mM) if not greater.…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Obtained ...mentioning
confidence: 99%
“…Thiazolidine-2,4diones (Glitazones) are an oral antidiabetic drugs that have attracted the attention for their excellent potential in controlling postprandial increase of glucose in blood without causing hypoglycemia (Bloomgarden et al, 2018) (Figure 1). Their flexible structure characterize thiazolidinediones (TZDs) by a wide range of pharmacological activities which include anti-hyperglycemic (Naim et al, 2017;Shrivastava et al, 2016), anti-inflammatory (Uwabagira et al, 2020), anti-obesity (George et al, 2021), anti-microbial (Yagnam et al, 2021), and anti-proliferative (Salamone et al, 2012) activities. Furthermore, TZDs derivatives also reported as a-glucosidase inhibition (Fettach et al, 2021).…”
Section: Introductionmentioning
confidence: 99%